Lipid infusion in the management of poisoning: a report of 6 canine cases. Issue 1 (11th July 2013) - Bates, N.; Chatterton, J.; Robbins, C.; Wells, K.; Hughes, J.; Stone, M.; Campbell, A.
Abstract : Intravenous administration of lipid is a relatively new treatment in the management of toxicity from lipophilic compounds. It is used in human medicine in the treatment of toxicity from lipophilic local anaesthetics and cardiotoxic drugs and can result in dramatic improvement in clinical status. We present six cases of poisoning in dogs successfully treated with lipid infusion after ingestion of ivermectin (3), moxidectin (2) and baclofen (1). The dogs ranged in age from eight weeks to 14 years, and weighed 4–30 kg. Intravenous lipid therapy was started between six and eight hours and 22 hours after ingestion, and all the dogs responded well. In four dogs, there was clinical improvement within one hour; one had improved within two hours and the other within 4.5 hours of lipid administration. The only adverse effect of lipid infusion reported was mild swelling and pain after extravasation in one case which resolved with conservative management. All the dogs were discharged within 24–52 hours after exposure (7–46 hours after the start of lipid administration), and none developed any apparent sequelae.